2011
DOI: 10.1007/s10546-011-9599-z
|View full text |Cite
|
Sign up to set email alerts
|

Modelling Local Sea-Breeze Flow and Associated Dispersion Patterns Over a Coastal Area in North-East Spain: A Case Study

Abstract: The structure and evolution of the sea breeze in the north-west part of the Mediterranean (Catalonia, north-east Spain) is studied both experimentally and, predominantly, using numerical models to increase understanding of sea-breeze structure and threedimensional (3D) pollution distributions in coastal environments. Sea-breeze components are modelled and analyzed using the fifth-generation Pennsylvania State University-National Centre for Atmospheric Research Mesoscale Model (MM5). The results show that the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…For this reason in the case of the wind direction a modification of the traditional formula of MB and MAGE has been applied [3] [71] [72].…”
Section: Data Sets and Model Evaluationmentioning
confidence: 99%
“…For this reason in the case of the wind direction a modification of the traditional formula of MB and MAGE has been applied [3] [71] [72].…”
Section: Data Sets and Model Evaluationmentioning
confidence: 99%
“…The SB has been widely studied due to its influence on air quality and pollution (Clappier et al, 2000;Talbot et al, 2007;Borge et al, 2008;Soler et al, 2011;Wang et al, 2013), the generation of wind energy offshore (Steele et al, 2013;Archer et al, 2014), the formation of convective systems and severe weather (Azorín-Molina et al, 2014;Comin et al, 2015), and the forecasting of maximum temperatures in locations close to the shore during hot spells (Meir et al, 2013). Besides, around 40% of the population lives within 100 km of the coast, and therefore its understanding and adequate representation in mesoscale numerical models is highly relevant.…”
Section: Sea Breezesmentioning
confidence: 99%
“…In this chapter we explore the characteristics of this mesoscale phenomenon on the Cantabrian coast of Spain, particularly on the Basque coast. The SB and its characteristics are well studied on the Mediterranean coast of Spain (Ramis and Romero, 1995;Azorín-Molina and Chen, 2009;Soler et al, 2011; Ponce de León and Orfila, 2013), but not so in the Cantabrian coast, perhaps due to a lower prevalence of fair-weather conditions during the summer period. However, it was found that the SB was one of the main drivers of pollution episodes in the industrialised metropolitan area of Bilbao (Alonso et al, 2000).…”
mentioning
confidence: 99%
“…Drobinski et al, 2006;Federico et al, 2010;Azorin-Molina et al, 2011) and to numerical modeling (e.g. Chen et al, 2011;Crosman and Horel, 2010;Grønås and Sandvik, 1998;Papanastasiou et al, 2010a;Rao et al, 2011;Soler et al, 2011).…”
Section: Introductionmentioning
confidence: 99%